Peningkatan Pengetahuan Remaja Putri tentang Hipnoterapi dengan Musik Instrumentalia Melayu Jambi dalam Mengatasi Dismenore - Gustina Gustina; Arifarahmi Arifarahmi (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Dysmenorrhea or menstrual pain is a stabbing pain that is felt in the lower abdomen and thighs, this occurs due to an imbalance of the hormone progesterone in the blood, resulting in pain arising. Almost all women have felt interference during menstruation in the form of menstrual pain (dysmenorrhea) with various levels, ranging from just aches in the pelvis from the inside to extreme pain. The prevalence of dysmenorrhea in adolescent girls is 74.42%. The highest proportion of dysmenorrhea was found in adolescents aged 14 and 16 years, had no family history of dysmenorrhea, menarche age 11-12 years, menstruation for 7 days or more, normal nutritional status, and adolescent girls who rarely exercised. The most complained and felt impact due to dysmenorrhea is limited physical activity, poor concentration and absence in the teaching and learning process. Non-pharmacologically, pain can be treated, one of which is with distraction techniques. The technique of distraction or distracting someone is the most effective to reduce pain by listening to classical music (mozart) and also back exercises. The purpose of this community service is to increase the knowledge of young women about hypnotherapy with Jambi Malay instrumental music in overcoming dysmenorrhea. The method / approach taken is to assess the knowledge of young women before and after education about hypnotherapy with Jambi Malay instrumental music in overcoming dysmenorrhea. After participating in a series of activities in accordance with the implementation plan, the results were obtained before good knowledge education was carried out 5 (23.8%) young women and less good 16 (76.6%) young women, after good knowledge education 21 (100%).